2020
DOI: 10.1016/j.oraloncology.2020.104844
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of international guidelines for tracheostomy in COVID-19 patients

Abstract: At this moment, the world lives under the SARS-CoV-2 outbreak pandemic. As Otolaryngologists -Head & Neck Surgeons, we need to perform and participate in examinations and procedures within the head and neck region and airway that carry a particularly high risk of exposure and infection because of aerosol and droplet contamination. One of those surgical procedures in demand at this moment is tracheostomy due the increasing ICU admissions. This review of international guidelines for tracheostomy in COVID-19 infe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 35 publications
4
51
0
5
Order By: Relevance
“… 9 10 Early guidelines recommended deferring tracheostomy in these patients beyond the first weeks of MV due to high early patient mortality and potential risks to proceduralists. 11–14 Consistent with reports from other centers, we observed that many intubated patients with COVID-19 infection require unusually high doses of sedation, increasing the risk of delirium, an independent predictor of longer lengths of stay, higher mortality, greater cost of care, and acquired dementia in ICU survivors. 15–19 Increased sedation requirements may contribute to failure to liberate patients with COVID-19 infection from ventilator support successfully.…”
Section: Introductionsupporting
confidence: 91%
“… 9 10 Early guidelines recommended deferring tracheostomy in these patients beyond the first weeks of MV due to high early patient mortality and potential risks to proceduralists. 11–14 Consistent with reports from other centers, we observed that many intubated patients with COVID-19 infection require unusually high doses of sedation, increasing the risk of delirium, an independent predictor of longer lengths of stay, higher mortality, greater cost of care, and acquired dementia in ICU survivors. 15–19 Increased sedation requirements may contribute to failure to liberate patients with COVID-19 infection from ventilator support successfully.…”
Section: Introductionsupporting
confidence: 91%
“…Performing tracheostomy in the COVID-19 era exemplifies how a previously straightforward clinical decision for an essential-elective procedure has been reimagined when the safety of more than just the patient must be considered. The balance of anticipated benefits and risks for major stakeholders (patient, health care system, and HCW) will vary between different locations during various stages of the COVID-19 pandemic as evidenced by a multitude of available guidelines 5 ( Table 4 ). A multidisciplinary team is essential in developing a center-specific protocol for COVID-19 tracheostomy with an indispensable role for simulation and team rehearsal.…”
Section: Discussionmentioning
confidence: 99%
“…Tracheostomy insertion and routine tracheostomy care are aerosol generating procedures and therefore high risk for COVID-19 transmission, particularly to health care workers (55). Most of the literature on tracheostomy insertion and care during the COVID-19 pandemic is in adults and from high income settings.…”
Section: Tracheostomiesmentioning
confidence: 99%